Development of A Creative Energy Gymnastics Learning Model for Elementary School Children - Pasha Aprilia; Ipang Setiawan (Journal of Physical Education Health and Sport, 2026)
Physical Education, Sports, and Health (  PE ) lessons in primary schools require imaginative teaching methods that are well suited to children's nature and current developments. This study aims to develop and test the effectiveness of Creative Energy Gymnastics as PE teaching material, particularly for rhythmic activities. The method used is Research and Development (R&D), which combines quantitative and qualitative elements. Data was collected through several techniques, such as observation, questionnaires, surveys, and assessment sheets, then analysed using descriptive methods in the form of percentages and qualitative analysis. The product was tested in two stages, first on a small scale, then on a large scale. The results were very positive, with interest and satisfaction levels reaching 68.75%, movement comprehension reaching 80.01%, gymnastics benefits reaching 75.37%, and attitude and cooperation reaching 80.01%, all of which were classified as good. Finally, Creative Energy Gymnastics was deemed very suitable as an innovative teaching method for physical education that is appropriate for primary school children.